Faculty Involvement for Creating Awareness about Social Responsibility - Patil, S. S.; Awati, J. S. (Journal of Engineering Education Transformations, 2015)
As an engineering faculty, always talks about obligation of an engineer for social development. It is the role of a teacher to encourage or involve the students in society related activities. This paper present community development related activities run by engineering faculty involving students. lt engages the students to look around community & find out the areas whereas human being and engineer can help the society. This paper deals contribution of engineering faculty.